(untitled) (Bangladesh Journal of Livestock Research, 2020)
The study was conducted at Bangladesh Livestock Research Institute to evaluate the productive and reproductive performances of 4 pure lines conserving for the production of next generation. A total of 2000 pedigree hatched day-old chicks were wing banded and reared up to 40 weeks of age. Data were kept on daily feed intake (g/bird/day), weekly body weight (g), age at sexual maturity (days), daily egg production (%) and egg weight (g). There were highly significant differences (p<0.01) in body weight at 38 weeks, age at sexual maturity, egg production up to 40 weeks and egg weight at 38 weeks of age among the treatment groups. There were no significant differences (P>0.05) in fertility, hatchability, dead in germ, sound chick and dead in shell percentage among the treatment except cull chicks where L1 showed the highest percent of cull chicks. Egg production at 23-28 and 35-40 weeks of age differ significantly (p<0.01) except at 29-34 weeks of age (p>0.05). Significant variations for FCR observed at 35-40 weeks of age while it was non-significant (p>0.05) at 23-28 and 29-34 weeks of age. It is revealed that line-2 is superior in terms of egg production, age at sexual maturity and egg mass where line-1 was better in terms of FCR value. Considering the results it may be concluded that there are significant variations exists regarding egg production performances among the experimental pure lines, thus could be utilized successfully for the production of high yielding strains through proper breeding programme. Bangladesh J. of Livestock Res. 20(1-2): 26-32, Jan-Dec 2013